2013
DOI: 10.1097/scs.0b013e31828f2e56
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radiofrequency and Intranasal Steroid Treatments on Respiratory and Olfactory Functions in Nasal Obstruction

Abstract: Although RFA may be more effective in the posterior region of the nasal cavity, INS and RFA used in the treatment of inferior concha hypertrophy both had favorable effects on respiratory function. Intranasal steroid treatment provided improved discrimination and total score values, whereas RFA treatment improved only odor identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The reduction of the severity of symptoms in the third month in this study was confirmed by Sozen et al with the exception that they analyzed the cases in the third month after the intervention and did not consider quality of life and rhinomanometry of patients (18). The present study was in agreement with Celiker et al study in reducing the severity of nasal hyperemia (19).…”
Section: Discussionsupporting
confidence: 90%
“…The reduction of the severity of symptoms in the third month in this study was confirmed by Sozen et al with the exception that they analyzed the cases in the third month after the intervention and did not consider quality of life and rhinomanometry of patients (18). The present study was in agreement with Celiker et al study in reducing the severity of nasal hyperemia (19).…”
Section: Discussionsupporting
confidence: 90%
“…[2][3][4] Intranasal glucocorticosteroids (INSs) are regarded as the most effective pharmacologic treatment for AR and are recommended by Allergic Rhinitis and its Impact on Asthma (ARIA) guidelines as first-line treatment. Although long-term use of steroid nasal sprays is often associated with side effects like bleeding, drying, and crusting, [4,5] intranasal glucocorticosteroids have a good safety profile. This is especially true for newer INSs (such as ciclesonide, mometasone furoate, and fluticasone furoate) which have systemic bioavailability lower than 1%.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true for newer INSs (such as ciclesonide, mometasone furoate, and fluticasone furoate) which have systemic bioavailability lower than 1%. [4] Sozen et al [5] compared the positive effects of nasal steroid spray and radiofrequency ablation for ITH and concluded that nasal steroids may be used to treat this condition. [5] Surgical treatment of ITH in the form of surface cautery is done with electrosurgical probe, laser, or cryoprobe.…”
Section: Discussionmentioning
confidence: 99%